2020
DOI: 10.1128/aac.01521-19
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial (TAURCAT Study) of Citrate Lock Solution for Prevention of Endoluminal Central Venous Catheter Infection in Neutropenic Hematological Patients

Abstract: Infection of long-term central venous catheters (CVCs) remains a challenge in the clinical management of cancer patients. We aimed to determine whether a lock solution with taurolidine-citrate-heparin would be more effective than placebo for preventing nontunneled CVC infection in high-risk neutropenic hematologic patients. We performed a prospective, multicenter, randomized (1:1), double-blind, parallel, superiority, placebo-controlled trial involving 150 hematological patients with neutropenia carrying nontu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 34 publications
0
17
0
12
Order By: Relevance
“…Fourteen articles (1219 patients) were included in the qualitative synthesis, nine (918 patients) of these articles were included in the quantitative synthesis. [57][58][59][60][61][62][63][64][65][66][67][68][69][70] [Figure 1]…”
Section: Study Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen articles (1219 patients) were included in the qualitative synthesis, nine (918 patients) of these articles were included in the quantitative synthesis. [57][58][59][60][61][62][63][64][65][66][67][68][69][70] [Figure 1]…”
Section: Study Selection Processmentioning
confidence: 99%
“…Of the 14 included articles, five (36%) had a blinded study design, of which four had a double-blinded design. [61,[66][67][68][69] Two (14%) non-blinded studies used an assessor-masked design to avoid bias. [62,64] The 14 included articles described patients receiving haemodialysis (n=5, 36%) or TPN (n=4, 29%), oncology patients (n=4, 29%), or a combination of these (n=1, 7%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Heparin lock solutions are commonly used, although saline solution might be a safe alternative as it proved non-inferior in terms of functional problems and CVC-related bacteremia in a randomized trial including 802 cancer patients with totally implantable venous access devices [181]. Taurolidinecitrate-heparin did not result in significantly less CVC hub colonization and CRBSI than placebo in neutropenic hematologic patients in a prospective multicenter trial involving 150 patients with non-tunneled CVCs [182]. Ethanol 70% lock solution has been studied in several randomized trials including heterogenous study populations with conflicting results.…”
Section: Antimicrobial Lock Solutions For Prevention Of Crismentioning
confidence: 99%
“…There are several current studies evaluating the prevalence, clinical features, etiology, and outcomes of cancer patients with bacteremia, with reported rates of septic shock varying by series from 6 to 57% (11,13,15,(18)(19)(20). Nevertheless, very few investigations have focused on patients presenting with sepsis or septic shock (31,36,48,49,52,55,87,88), and among these, some were retrospective, some used different sepsis definitions, and some did not provide comprehensive data.…”
Section: Characteristics Etiology and Outcomes Of Sepsis In Cancer mentioning
confidence: 99%
“…Of special concern is the widespread emergence and dissemination of multidrug-resistant (MDR) Gram-negative bacilli (GNB), which are a common cause of infection and sepsis in patients with cancer. Several investigators have reported high rates of bacteremia due to extended-spectrum β-lactamase (ESBL)producing Enterobacterales (10-13), MDR Pseudomonas aeruginosa (MDR-PA) (12,(14)(15)(16)(17), and carbapenem-resistant Enterobacterales (CRE) (18)(19)(20)(21)(22), among others, against which there are few treatment alternatives. This is of paramount importance because inadequate initial empirical antibiotic therapy can increase mortality when patients with cancer have infection due to MDR-GNB (11,(13)(14)(15)(16)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%